Demonstration of antibodies against Yersinia enterocolitica lipopolysaccharide in human sera by enzyme-linked immunosorbent assay. - Gripenberg, M (1979)
Antibodies against Yersinia enterocolitica serotype O:3 lipopolysaccharide present in sera from patients with Yersinia infection were studied by using an enzyme-linked immunosorbent assay. Of the sera with significant bacterial agglutination titers against Y. enterocolitica type O:3, 86% contained anti-lipopolysaccharide antibodies of the immunoglobulin G class. With the sera of some patients, we demonstrated increasing anti-lipopolysaccharide antibody levels of immunoglobulin G class in spite of decreasing bacterial agglutination titers. The assay was specific for lipopolysaccharide from Y. enterocolitica type O:3, and in inhibition experiments lipopolysaccharide could be detected in amounts of greater than or equal to 0.5 micrograms/ml.